Experimental study on the influence of cyclic compaction on the fiber-bed permeability, quasi-static and dynamic compaction responses. (October 2019) - Kabachi, M.A; Danzi, M.; Arreguin, S.; Ermanni, P.
Abstract: Fiber-reinforcements' permeability and compressibility are crucial parameters in Liquid Composite Molding Processes, as they represent the main textile properties that influence the behavior of the injected resin. Before designing LCM molds and optimizing manufacturing processes, permeability and compaction characterizations are performed; however, the results obtained often show considerable deviations. One reason for this behavior is the variable compaction histories of fiber-beds, which can be altered during storage or handling. This work presents a novel method to normalize compaction histories through cyclic compaction, thus increasing the reproducibility of compaction and through-thickness permeability responses. It also shows how fiber-bed's viscoelasticity can be reduced with minor influence on permeability. It is greatly beneficial in developing processing routes for vacuum assisted processes, and for future compaction or permeability benchmarks, in defining optimal characterization methods. It provides also solid basis for the comparison and validation of compaction and through-thickness permeability models with reduced measurement errors.